Managing CO2 Emissions through Focus on Energy Policies: Fresh Evidence from Iran’s Agriculture Sector - Parisa Pakrooh; Esmaeil Pishbahar; Babollah Hayati; Javad Nematian (Environmental Energy and Economic Research)
CO2 emissions as one of the environmental problems have intensified in the agriculture sector of Iran due to the increase in fossil energy consumption. Increasing the unequal distribution of CO2 emissions and energy consumption requires a deep understanding of the effective and ineffective policies and plans. Therefore, this study aimed to analyze the effect of energy-related policies, plans, different kinds of energy (including gasoline, natural gas, and electricity) in the agriculture sector of Iran’s provinces during 2001-16. To consider the regional differences, the Theil index, used to measure inequalities, and panel data approaches were applied to evaluate the effects of policies, plans, and inequalities on consumption. According to the results, first, the Theil index highlighted inequalities in energy consumption and CO2 emissions. Provinces in a similar population or GDP grouping methodology have not a uniform distribution in energy consumption and CO2 emissions. The estimated Fixed-Effect model for gasoline consumption indicated that some of the gasoline policies were not effective; however some of them could smooth the consumption. Subsidy removal phases had reduction effects on gasoline, but it would have a helpful impact if the difference in energy consumption had been considered. However, in the case of natural gas and electricity, policies were a great motivation to users. In summary, most of the policies were unsuccessful as they were not enough to control consumption and emissions as well, replaced the new non-renewable resources like natural gas and electricity, and intensified the inequalities. However, price-related policies could have significant effects on consumption.